EFFECT OF MARKETING MIX ON CONSUMER PURCHASE DECISIONS IN PT. SURACO JAYA ABADI MOTOR ANTANG MAKASSAR BRANCH - nurinaya, nurinaya; Safitri, Dewi (Jurnal Ekonomi Balance, 2018)
The purpose of this study is intended to determine the effect of the marketing mix of products, prices, promotions and distribution of consumer purchasing decisions at PT. Suraco Jaya Abadi Motor Branch, Antang Makassar. The study was conducted at PT. Suraco Jaya Abadi Motor Branch, Antang Makassar. Data collection methods used in this study are primary data which is data that is directly taken from the object of research using observations and questionnaires filled out by respondents namely consumers of PT. Suraco Jaya Abadi Motor Branch, Antang Makassar. The analytical methods used to solve problems and prove hypotheses include index number analysis, validity test, reliability test, multiple linear regression analysis and hypothesis testing which include t test, F test, and coefficient of determination (R2). The results of the study concluded that the marketing mix of products, prices, promotions and distributions affected the consumer's purchasing decisions at PT. Suraco Jaya Abadi Motor Branch, Antang Makassar. Based on the results of the calculation of the coefficient of determination test (R2) it can be seen that the coefficient of determination (R2) obtained is 0.446. This means that 44.60% of purchase decision variables can be explained by variations of product, price, promotion and distribution variables, while 55.40% is explained by other variables not included in this study.